Unexpected super spy - Mian, Zanib (London: Hodder Children's Books, 2020)
Omar and his friends have been saving up their pocket money for ages so they can have the world's most epic Nerf Blaster battle. But when Omar discovers that his mosque is in trouble, they decide to donate their pennies to help save it. Then they try to raise some more money by: doing some chores (boorrring), selling some home-made cookies (deeelicious) and holding a talent contest (YESSSSSSS). Everything goes PERFECTLY, until the money mysteriously goes missing. Can they work out who has taken it in time to stop the mosque closing down? And what exactly is Omar's sister Maryam hiding in her room?
Keywords: Children's stories